Codes of forest practice and related research needs. - Turnbull, J.W.; Vanclay, J.K. (1999)
This paper aims to set codes of forest practice in the framework of the evolving debate on sustainable forest management. Codes of forest practice are sets of regulations or guidelines developed by governments or other organisations to assist forest managers select practices to be followed when carrying out forest management and utilisation operations. These practices, when correctly applied, should meet standards for sustainable forest management. A code of practice is also a form of forest policy typically used to promote certain environmental benefits and the codes are regarded as important measures in moving towards sustainable forest management. They are based on the best knowledge available to ensure forests are well managed. In many countries the pressures from environmental activists to improve forest management practices began in the 1970s. In Australia, CSIRO published environmental guidelines for forest harvesting in 1979 and throughout the 1980s most Australian States developed codes of forest practices, principally directed at logging or harvesting forests. In the United States many forestry authorities published guidelines and best management practices from 1988 onwards, but Oregon developed the first comprehensive forestry practices Act in 1971. In the tropics, buoyant world timber markets and weak forest regulatory authorities led to deteriorating standards of timber harvesting and utilisation, and the gap, is widening between the principles of sustainable forest management and forest management practices. ITTO produced general guidelines for management of natural forests, planted forests and conservation of biological diversity in tropical forests. Regional codes of practice for the South Pacific and Asia-Pacific have and are being developed. The paper concludes that sustainability continues to be the single most important principle to guide forest management and management will need to continuously challenge and evaluate its own codes of forest practices.